Ruska (русская) czy rosyjska (российская), czyli dylematy rosyjskiej polityki historycznej - Zielińska, Julita (Polski Przegląd Stosunków Międzynarodowych, 2018)
Pусская or российская – dilemmas of Russian Historical Policy Historical policy is a relatively new phenomenon, the escalation of which is due at the beginning of the 21st century. Although it is a new area of activity of the state, it has become present in public discourse, particularly in the Central and Eastern European states. Historical policy in these countries has taken on a pejorative meaning and has become an instrument of manipulating history, for instance, to fight against political opponents. Taking into account the above factors, this article focuses on Russia, a once great empire that has become the subject of criticism and accusations. The states of the former Soviet Union rejected a „common heritage” and began to perceive Russia as an occupying force. Therefore, this article focuses on Russian historical policy – its challenges and dilemmas. At the beginning of the text is also the question about the nature of Russian historical policy – whether it is more русская or rather российская. By analysing such problems as: Russian imperialism, confusion around the Russian identity, and the narrow range of historical symbols, I will attempt to answer the above question.